2013
DOI: 10.1289/ehp.1204951
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Encoding Potential Mercury Transporters and Urine Mercury Concentrations in Populations Exposed to Mercury Vapor from Gold Mining

Abstract: Background: Elemental mercury (Hg0) is widely used in small-scale gold mining. Persons working or living in mining areas have high urinary concentrations of Hg (U-Hg). Differences in genes encoding potential Hg-transporters may affect uptake and elimination of Hg.Objective: We aimed to identify single nucleotide polymorphisms (SNPs) in Hg-transporter genes that modify U-Hg.Methods: Men and women (1,017) from Indonesia, the Philippines, Tanzania, and Zimbabwe were classified either as controls (no Hg exposure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Recent studies in Slc22a6 ( Oat1 )-knockout mice, or in tissues derived from such mice, have shown impaired handling of many of these compounds, as well as of environmental toxins 35,38,40,6163 . For example, mercury, which can cause kidney and nervous system toxicity and remains a major environmental concern, is thought to be conjugated in vivo to cysteine (among other molecules); it is effectively ‘handled’ by SLC22A6 in a manner similar to an organic anion 57,63,64 . The Slc22a6 ( Oat1 )-knockout mouse kidney is notably protected from mercury toxicity because mercury conjugates cannot enter kidney proximal tubule cells from the blood side, owing to the lack of SLC22A6 in these animals 63 .…”
Section: Slc and Abc Drug Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Slc22a6 ( Oat1 )-knockout mice, or in tissues derived from such mice, have shown impaired handling of many of these compounds, as well as of environmental toxins 35,38,40,6163 . For example, mercury, which can cause kidney and nervous system toxicity and remains a major environmental concern, is thought to be conjugated in vivo to cysteine (among other molecules); it is effectively ‘handled’ by SLC22A6 in a manner similar to an organic anion 57,63,64 . The Slc22a6 ( Oat1 )-knockout mouse kidney is notably protected from mercury toxicity because mercury conjugates cannot enter kidney proximal tubule cells from the blood side, owing to the lack of SLC22A6 in these animals 63 .…”
Section: Slc and Abc Drug Transportersmentioning
confidence: 99%
“…In addition, coding or non-coding single-nucleotide polymorphisms (SNPs) that result in clinical phenotypes have been reported for SLC22A6 and SLC22A8 (REFS 39,64,78) (TABLE 2). Although more extensive phenotypic analyses of the effects of OAT SNPs needs to be performed, these limited studies seem to be consistent with the in vitro and in vivo knockout data on their role in drug and toxin handling.…”
Section: Slc and Abc Drug Transportersmentioning
confidence: 99%
“…For example, mercury exists in the blood in thiol conjugates (with glutathione and cystathione), which effectively act like organic anions. OAT1 and OAT3 appear to be the major transporters involved in elimination of mercuric conjugates, which can lead to renal and central nervous system toxicity following mercurial exposure (48)(49)(50)(51). The proximal tubule of the kidney of the Oat1 knockout mouse is largely resistant to nephrotoxic damage that occurs from systemic administration of mercuric chloride (Figure 3) (52).…”
Section: Drugs and Toxinsmentioning
confidence: 99%
“…Early studies of transporter polymorphisms raised the possibility that multiple SNPs in basolateral (e.g., OAT1 and OAT3) (82,83) and apical (e.g., URAT1, OAT4, MRP2, and MRP4) drug transporters may affect the net transport of drugs, toxins, and metabolites from blood to urine (50,84). In addition, noncoding SNPs that regulate drug transporter expression might be particularly important (82,85).…”
Section: Pharmacogenomic and Toxicogenomic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation